Direct on-the-spot detection of SARS-CoV-2 in patients. Issue 14 (August 2020) - Ben-Assa, Nadav; Naddaf, Rawi; Gefen, Tal; Capucha, Tal; Hajjo, Haitham; Mandelbaum, Noa; Elbaum, Lilach; Rogov, Peter; King, Daniel A; Kaplan, Shai; Rotem, Assaf; Chowers, Michal; et al.
Many countries are currently in a state of lockdown due to the SARS-CoV-2 pandemic. One key requirement to safely transition out of lockdown is the continuous testing of the population to identify infected subjects. Currently, detection is performed at points of care using quantitative reverse-transcription PCR, thus requiring dedicated professionals and equipment. Here, we developed a protocol based on reverse transcribed loop-mediated isothermal amplification for the detection of SARS-CoV-2. This protocol is applied directly to SARS-CoV-2 nose and throat swabs, with no RNA purification step required. We tested this protocol on over 180 suspected patients, and compared the results to those obtained using the standard method. We further succeeded in applying the protocol to self-collected saliva samples from confirmed cases. Since the proposed protocol can detect SARS-CoV-2 from saliva and provides on-the-spot results, it allows simple and continuous surveillance of the community. Impact statement: Humanity is currently experiencing a global pandemic with devastating implications on human health and the economy. Most countries are gradually exiting their lockdown state. We are currently lacking rapid and simple viral detections, especially methods that can be performed in the household. Here, we applied RT-LAMP directly on human clinical swabs and self-collected saliva samples. We adjusted the method to allow simple and rapid viral detection, with no RNA purification steps. By testing our method on over 180 human samples, we determined its sensitivity, and by applying it to other viruses, we determined its specificity. We believe this method has a promising potential to be applied world-wide as a simple and cheap surveillance test for SARS-CoV-2.